2010
DOI: 10.1111/j.1476-5381.2010.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of persistent sodium current by F 15845 prevents ischaemia‐induced arrhythmias

Abstract: BACKGROUND AND PURPOSEMyocardial ischaemia is associated with perturbations of electrophysiological profile of cardiac myocytes. The persistent sodium current (INap) is one of the major contributors to ischaemic arrhythmias and appears as an attractive therapeutic target. We investigated the effects of F 15845, a new anti-anginal drug on INap and in integrative models of INap-induced arrhythmias. EXPERIMENTAL APPROACHSodium current was investigated using patch clamp technique on wild-type and DKPQ-mutated hNav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Unlike ranolazine [18] , 18β-GA produced a potent tonic block of I Na,L , which resulted in stronger anti-arrythmic effects. Recently, a more selective potent I Na,L blocker, F15845, also characterized by tonic blockade, has been demonstrated to be effective in preventing ischemia-induced arrhythmia [30] . HERG expresses I Kr , and blockage of HERG is believed to cause LQT, which can induce EAD and a Torsades de-Pointestype of ventricular arrhythmia, as observed after treatment …”
Section: Discussionmentioning
confidence: 99%
“…Unlike ranolazine [18] , 18β-GA produced a potent tonic block of I Na,L , which resulted in stronger anti-arrythmic effects. Recently, a more selective potent I Na,L blocker, F15845, also characterized by tonic blockade, has been demonstrated to be effective in preventing ischemia-induced arrhythmia [30] . HERG expresses I Kr , and blockage of HERG is believed to cause LQT, which can induce EAD and a Torsades de-Pointestype of ventricular arrhythmia, as observed after treatment …”
Section: Discussionmentioning
confidence: 99%
“…Many local anesthetic and antiarrhythmic agents have greater potency to block I NaL than peak I Na (I NaP ). Certain compounds, such as ranolazine (Gupta et al, 2015) and F15845 (3-(R)-[3-(2-methoxyphenylthio-2-(S)-methylpropyl]amino-3,4-dihydro-2H-1,5 benzoxathiepine bromhydrate) (Pignier et al, 2010), are described as preferential I NaL blockers.…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent publication, a novel small molecule targeting multiple mechanisms involved in atrial fibrillation showed a 3-fold higher I Na, late inhibition over peak I Na inhibition, in addition to other ion channel blocking properties, and exhibited efficacy against AF in a chronic atrial tachypacing induced AF dog model [233]. Another novel I Na, late inhibitor, F 15845, reduced the incidence of coronary artery ligation induced arrhythmias in rats [234]. Based on these data, inhibition of I Na, late represents a promising approach for the treatment of both ventricular and atrial arrhythmias in HF.…”
Section: Na Late Inhibitorsmentioning
confidence: 99%